2017
DOI: 10.1002/pon.4484
|View full text |Cite
|
Sign up to set email alerts
|

Positive aspects of having had cancer: A mixed‐methods analysis of responses from the American Cancer Society Study of Cancer Survivors‐II (SCS‐II)

Abstract: This analysis provides new information about cancer survivors' perceptions of positive aspects from their cancer and factors associated with benefit finding and personal growth. This information can be useful in further refining quality-of-life measures and interventions for cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…The mean score on the PII‐faith was 13.3 (5.7) with roughly 70% of the sample endorsing at least one item on the scale. Although, apart from Salsman et al, there are no independent reports of the impact of cancer on religious faith, consistent with the current study are the reports of positive changes in the areas of post‐traumatic growth and/or benefit finding following cancer, both of which include one or more aspects of R/S …”
Section: Discussionsupporting
confidence: 85%
“…The mean score on the PII‐faith was 13.3 (5.7) with roughly 70% of the sample endorsing at least one item on the scale. Although, apart from Salsman et al, there are no independent reports of the impact of cancer on religious faith, consistent with the current study are the reports of positive changes in the areas of post‐traumatic growth and/or benefit finding following cancer, both of which include one or more aspects of R/S …”
Section: Discussionsupporting
confidence: 85%
“…Patients of both genders have conveyed the importance of compassion when coping with their illness. 16,27,28 The present study found that women expressed more compassion in response to NIH-HEALS, suggesting that perhaps women in our sample may more readily identify compassion for others in their healing process than men. However, this does not mean that this construct is unimportant in men.…”
Section: Gender Differences and Healingmentioning
confidence: 46%
“…Both men and women endorsed Medical Support items that describe support and reliable relationships with medical care providers. 16 The difference between genders in the Reflection & Introspection factor of NIH-HEALS in the present study was due to differences in response to four items that capture compassion, gratitude, enjoyment of activities that involve the mind and body, and a desire to be more positive. Patients of both genders have conveyed the importance of compassion when coping with their illness.…”
Section: Gender Differences and Healingmentioning
confidence: 62%
See 1 more Smart Citation
“…Post‐traumatic growth is a term used to describe the positive consequences that emerge through the processing of a traumatic experience that lead to subsequent growth and personal development (Calhoun & Tedeschi, ). The American Cancer Society Study of Cancer Survivors‐II ( n = 5,149) found that gratitude and appreciation for life were the most frequently endorsed themes (Adorno et al, ). In some studies, the majority of adolescent cancer survivors report personal growth (Barakat, Alderfer, & Kazak, ), including long‐term survivors of osteosarcoma (Barakat et al, ; Yonemoto et al, ).…”
Section: Introductionmentioning
confidence: 99%